SOME ASPECTS OF DIAGNOSIS AND SURGICAL TREATMENT OF UPPER EXTREMITY NERVE INJURIES - M.KH. MALIKOV; M.A. KHASANOV; KH.F. MIRZOBEKOV; KH.I. SATTOROV (Avicenna Tajik State Medical University, 2020)
The review addresses the issues of diagnosis and surgical treatment of concomitant chronic injuries of the upper limb nerves. The role of modern additional research methods in damage to the nerves is shown, and, depending on the prevalence of damage to certain structures, the value of each technique is shown. A detailed description of the clinical manifestations of sensory and motor disorders of the hand is given. The reasons for the diagnostic and tactical errors made during the examination and treatment of victims at the stages of medical evacuation are especially indicated. Depending on the nature and the duration of the injury, the expediency of using traditional and microsurgical methods of correction for chronic damage to the nerves is shown. The issues of neurotization and tendomuscular transposition are highlighted, and indications for their use are determined.